Paradigmity of the Process of Educational and Cognitive Activities of Students in the Context of Different Approaches - Golodiuk, Larysa (Pedagogical Discourse, 2017)
The essence of concept «paradyhm» and the paradigmity of the process of students’ educational and cognitive activities in the context of student oriented, systematic, synergetic, cognitive, competence and spatial and environmental approaches are defined in the article by the author. The scientific resources which consider educational paradyhms, singled out in their to picul content key ideas, accepted in the scientific community have been analyzed. Arrangement based on common semantic accents has been made. It has been done with the focus on: the results of education, thought processes, value orientations, factors of students’ development, learning tools, content, standard principles of public management society, accountability of educational processes, subject of activities, conditions which promote child development. It was found that the accumulation of key ideas of such educational paradyhms as kalokahatyvnist’, dogmatic teaching, explanatory illustrative training, adaptive learning, developing education, cognitive and cultural ones was provided by the paradyhmalnist’ of the process of students’ educational and cognitive activities. Key words: paradyhm, paradigmity, student oriented approach, systematic approach, synergetic approach, cognitive approach, competence approach, spatial and environmental approach.